2020
DOI: 10.47862/apples.99132
|View full text |Cite
|
Sign up to set email alerts
|

Normativity in English oral production in Finland and Japan

Abstract: This research examines the effects of normativity on difficulties experienced with English oral production in Finland and Japan. Moyer’s classification of factors influencing second language acquisition (2004) as well as language ideology theory (Garrett, 2010; Milroy, 2007) are used as a framework for an analysis of 56 semi structured interviews with Finnish and Japanese adult learners of intermediate level English. Self-reported experiences related to speaking English were annotated with appropriate codes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…On the other hand, Paakki (2020) called it "normativity," which is defined as the "idealization of standard target language (TL) accents, and standard TL models that are free from dialect features, learner errors, spoken-language-like colloquialisms or imperfectness…" (p. 24). Another factor mentioned by Paakki (2020) is the instruction and input factors; this study showed that both Finnish and Japanese students were taught based on accuracy rather than fluency, where language test-taking activities prevailed over oral production tasks. These factors hindered their performance and their self-confidence in their speaking ability.…”
Section: Oral Productionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, Paakki (2020) called it "normativity," which is defined as the "idealization of standard target language (TL) accents, and standard TL models that are free from dialect features, learner errors, spoken-language-like colloquialisms or imperfectness…" (p. 24). Another factor mentioned by Paakki (2020) is the instruction and input factors; this study showed that both Finnish and Japanese students were taught based on accuracy rather than fluency, where language test-taking activities prevailed over oral production tasks. These factors hindered their performance and their self-confidence in their speaking ability.…”
Section: Oral Productionmentioning
confidence: 90%
“…Even though English is a language studied profusely worldwide (Fregonese, 2017), many students of this language have difficulty speaking it (Juhana, 2012;Paakki, 2020). Both Brown (2000) and Paakki (2020) addressed the factors which hinder students' oral production skills. Brown (2000) called it the "language ego," which is students' idea that they are what they speak.…”
Section: Oral Productionmentioning
confidence: 99%
“…On the other hand, Paakki (2020) called it "normativity," which is defined as the "idealization of standard target language (TL) accents, and standard TL models that are free from dialect features, learner errors, spoken-language-like colloquialisms or imperfectness…" (p. 24). Another factor mentioned by Paakki (2020) is the instruction and input factors; this study showed that both Finnish and Japanese students were taught based on accuracy rather than fluency, where language test-taking activities prevailed over oral production tasks. These factors hindered their performance and their self-confidence in their speaking ability.…”
Section: Oral Productionmentioning
confidence: 90%
“…Even though English is a language studied profusely worldwide (Fregonese, 2017), many students of this language have difficulty speaking it (Juhana, 2012;Paakki, 2020). Both Brown (2000) and Paakki (2020) addressed the factors which hinder students' oral production skills. Brown (2000) called it the "language ego," which is students' idea that they are what they speak.…”
Section: Oral Productionmentioning
confidence: 99%
“…After all, English is the most studied foreign language in Finland in all educational levels and enjoys a popular and valued status in society (McCambridge & Saarinen, 2015;Ruohotie-Lyhty, 2021). Yet, typically, Finnish speakers overall have a more passive style of communication (Paakki, 2020), which can be surprising or disheartening to foreign lecturers. However, the issue is not exclusive to Finland as in other European EMI programmes similar occurrences of unwillingness to communicate have been recorded (e.g., Chien & Valcke, 2020).…”
Section: Discussionmentioning
confidence: 99%